2015
DOI: 10.4081/idr.2015.5901
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio Vulnificus Necrotizing Fasciitis Associated with Acupuncture

Abstract: Necrotizing fasciitis is a severe life-threatening infection of the deep subcutaneous tissues and fascia. Infection with Vibrio vulnificus, a halophilic Gram-negative bacillus found worldwide in warm coastal waters, can lead to severe complications, particularly among patients with chronic liver diseases. We herein present an unusual case of necrotizing fasciitis caused by V. vulnificus triggered by acupuncture needle insertion. The patient, who suffered from diabetes mellitus and nonalcoholic fatty liver dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Necrotizing fasciitis (NF), a rare and life-threatening infection of deep soft tissues and fascia, is rarely reported as a consequence of needle electromyography [ 2 ]. Some other similar procedures, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Necrotizing fasciitis (NF), a rare and life-threatening infection of deep soft tissues and fascia, is rarely reported as a consequence of needle electromyography [ 2 ]. Some other similar procedures, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some other similar procedures, e.g. acupuncture, have been previously reported as a cause of a deep soft tissue infection, such as necrotizing fasciitis [ 2 - 3 ]. Infectious organisms due to acupuncture needles have included Escherichia coli and Mycobacterium tuberculosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Interestingly, one reported case of necrotizing fasciitis associated with V vulnificus infection was triggered by acupuncture. 16 The patient worked in a fish hatchery, where he was exposed to V vulnificus, and subsequent acupuncture led to the inoculation of bacteria into his bloodstream. This case raises the important point that we typically sequence the pathogenesis of V vulnificus infection as a patient having an open wound that is subsequently exposed to contaminated water; however, it also can follow the reverse sequence.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Symptoms of primary septicemia include fever, chills, nausea, and hypotension. Wound infection is generally acquired through the exposure of a preexisting wound to contaminated seawater or shellfish, resulting in fulminant necrotizing skin and soft tissue infections (Huang et al., ; Kotton, Soboh, & Bisharat, ). Previous reports indicated that V. vulnificus can only affect humans and other primates.…”
Section: Introductionmentioning
confidence: 99%